Ultrahigh pseudocapacitance of mesoporous Ni-doped Co(OH)2/ITO nanowires - Tai Dam, Duc (2013)
Mesoporous Ni-doped Co(OH)2 was uniformly deposited along indium-tin oxide nanowires (ITO NWs) which were directly grown on titanium substrates by chemical vapor deposition followed by potentiostatic electrodeposition through a hexagonal liquid crystalline phase of a nonionic surfactant. The as-synthesized electrode is a network composed of ultrathin nanosheets with thickness of about 10 nm containing pores in the diameter range of 2–3 nm. The mesoporous nanowire electrode demonstrates extremely high specific capacitance of 2052 F g−1 at discharge current density of 1 A g−1 in an aqueous KOH solution. Moreover, the nanowires with mesoporous nanosheets exhibit superior pseudocapacitive behavior, lower capacitance fading, and better rate performance than films with mesoporous nanosheets.